Pengaruh bauran pemasaran terhadap keputusan konsumen menggunakan jasa angkutan bis trayek Pontianak-Sintang kelas executive pada PT. ADAU KAPUAS - Sinhan 01; Hajijah A (JURNAL MANAJEMEN MOTIVASI, 2015)
This study aims to determine the effect of marketing mix consisting of product, price, promotion, place, people, process, physical evidence, the consumer decision to use bus transportation services PT.ADAU KAPUAS route Pontianak-Sintang. The population in this study are all passengers using bus transportation services route Pontianak-Sintang class executive at PT. Adau KAPUAS. While the sample is part of the number and characteristics of being owned by the population. The samples used were asmany as 100 people with sampling techniques. The sampling technique used is incidental sampling is according Sugiono (2003: 65)  "sampling technique based on the chance that anyone who by chance met the researchers used as a sample. Simple Linear Regression Test results indicate the following matters, or the estimated regression equation explains the data processing is written Y = 1.062 + 0,796X that if the marketing mix of zero (0), then the decision of consumers using bus transportation services route Pontianak-Sintang executive class PT. Adau KAPUAS of 1,062.Uji coefficient of determination (R²) indicate that as many as 23.8% (1 x 0.238 x 100%)  the decision of consumers using bus transportation services route Pontianak-Sintang influenced by the marketing mix and the remaining 76.2,% (1 - 0.238 x 100%)  influenced by factors or other variables out of the study. From the results of regression analysis showed that test the feasibility of the model independent variables have an effect on the dependent variable. This is evident from the calculated F value of 30.636> F table 2,10 and has a significant value (sig)  of 0.000 which is less than 0.05, meaning that the simple linear regression model can be used to predict consumer decisions are influenced by the marketing mix.